2006
DOI: 10.1007/s10661-006-9267-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis for spring bloom and nutrient limitation in Xiangxi bay of three Gorges Reservoir

Abstract: The spatial and temporal dynamics of physical variables, inorganic nutrients and phytoplankton chlorophyll a were investigated in Xiangxi Bay from 23 Feb. to 28 Apr. every six days, including one daily sampling site and one bidaily sampling site. The concentrations of nutrient variables showed ranges of 0.02-3.20 mg/L for dissolved silicate (Si); 0.06-2.40 mg/L for DIN (NH 4 N + NO 2 N + NO 3 N); 0.03-0.56 mg/L for PO 4 P and 0.22-193.37 μg/L for chlorophyll a, respectively. The concentration of chlorophyll a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 22 publications
2
71
0
Order By: Relevance
“…However, in Xiangxi Bay, nitrogen has been considered to be the primary nutrient limiting phytoplankton growth (Ye et al 2007;Zhou et al 2009). The Xiangxi Bay was subject to serious phosphorus pollution mainly from a large number of phosphorous industry wastewater and domestic sewage ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in Xiangxi Bay, nitrogen has been considered to be the primary nutrient limiting phytoplankton growth (Ye et al 2007;Zhou et al 2009). The Xiangxi Bay was subject to serious phosphorus pollution mainly from a large number of phosphorous industry wastewater and domestic sewage ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the spatial extents and frequency of algal blooms exhibited an increasing trend in last 3 years. Except for some of the earlier studies on algal blooms investigation and water quality assessment (Kuang et al 2004;Zhou et al 2006;Ye et al 2007), there were no studies focusing on spring phytoplankton blooms and its relationship with environment in Xiangxi Bay. However, determining the ongoing changes of environmental factors that primarily affect spring phytoplankton blooms under the given interactions between reservoir formation and river flow is an important first step in monitoring the development while these data can at a later date serve effectively reservoir management strategies.…”
Section: Introductionmentioning
confidence: 99%
“…A long reservoir-bay can be regarded as the canyon-shaped reservoir without dam which exhibited marked longitudinal gradients . For example, Ye et al (2006Ye et al ( , 2007 analyzed the spatial distribution of nutrient in Xiangxi Bay of Three-Gorge Reservoir (TGR, China), and found that phosphorus increase and nitrogen decrease along longitudinal gradients from the mouth to the headwater. Xu et al (2009a) also illustrated the longitudinal gradients in inorganic suspended particles of Xiangxi Bay, one of non algal absorbing components which influence the underwater light condition for phytoplankton growth.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, there have been no algal blooms reported until now in the mainstream of TGR. Many examples of algal blooms from Xiangxi Bay were published in Chinese and international journals (Ye et al, , 2007Wang et al, 2009;Xu et al, 2009cXu et al, , 2010cZhang et al, 2009). For example, daily and weekly observation during spring of the year 2005 showed that algal blooms occurred in the Xiangxi Bay with maximum chlorophyll a of 179.39 mg/L (Ye et al, , 2007.…”
Section: Algal Bloomsmentioning
confidence: 99%
“…The impacts of TGD on ecological processes of water body have caused concern to aquatic ecologists worldwide (Cai and Hu, 2006). Many ecological studies of TGR after the first impoundment have been published in Chinese and international journals, including suspended solids (Xu et al, 2009a), water eutrophication (Cai and Hu, 2006;Xu et al, 2010a), algal blooms (Ye et al, , 2007Xu et al, 2009b,c), phytoplankton (Zeng et al 2006), zooplankton (Xue et al, 2006), and macroinvertebrates (Shao et al, 2008). For example, it was found that water residence time is an important regulatory factor for seasonal dynamics of suspended solids (Xu et al, 2009a), trophic status (Xu et al, 2010a) and water clarity (Xu et al, 2010b) after the first impoundment.…”
Section: Introductionmentioning
confidence: 99%